P287 The impact of restricted access to targeted therapies for rheumatoid arthritis on rheumatologists and the service they can provide. (23rd April 2022) - Walker, David; Robinson, Sandra
Abstract: Background/Aims: Just under half of the clinical commissioning groups (CCGs) in England restrict the number of targeted therapies that can be prescribed for rheumatoid arthritis (RA) before an individual funding request (IFR) is required. We were interested to explore the impact of this on rheumatology services and rheumatologists themselves. Methods: A national survey of rheumatologists who prescribe high-cost drugs was developed to explore prescribing restrictions by CCGs, the impacts on the service and the strategies adopted to mitigate this. Results from the survey were then used to develop an interview schedule for semi structured interviews with five rheumatologists to explore this in more detail. Results: A total of 53 rheumatologists started the survey. 23 participants (44%) were restricted in their use of high-cost drugs. Restrictions were mainly by total number rather than mode of action. For 46, (88%) restrictions were communicated through local guidelines. 41% had additional local restrictions either through their pharmacy (5%), local pathways (10%) or a multi-disciplinary team meeting (MDT; 27%). 51% routinely discussed high-cost drugs with colleagues, with 21% discussing only complicated patients. The effect on the service was rated: a lot = 43%; moderately =24%; and a little or not = 7%. 95% said it affected their practice e.g., persisting with ineffective therapy. Blueteq was used by 69%; 29% were negative or very negative about it, 29% were neutral, and 23% were positive about it. 19% had it completed by someone else. Strategies for mitigating the restrictions included: 43% of participants had used a foot instead of a hand in the DAS28; 68% had changed diagnostic category to justify treatment; 51% had negotiated a local pathway. Three themes emerged from the semi-structured interviews. Theme 1) Persistence with partially effective therapy was used to avoid running out of options. There was genuine distress about the poor service that was being delivered. Theme 2) IFRs do not work but negotiating alternative pathways with the CCG can. Theme 3) Bluetec is an extra burden in the process but is OK if you do not have to fill it in yourself. Conclusion: Restricting the number of targeted therapies that can be prescribed for RA has a detrimental effect on the service and the prescribers involved which often results in persistence with partially effective therapies. Continuing partially effective therapies is not satisfactory if there may be more effective therapies available. Acknowledgements: On behalf of the EVA-RA Joint Working Group. Disclosure: D. Walker: Consultancies; Galapagos, Eli Lilly. S. Robinson: None.